Synthesis of a fluorinated graphene oxide–silica nanohybrid: improving oxygen affinity. Issue 52 (11th May 2016) - Maio, A.; Giallombardo, D.; Scaffaro, R.; Palumbo Piccionello, A.; Pibiri, I.
Abstract : An easy method to selectively introduce specific fluorotails into a graphene oxide–silica nanohybrid. Fluoro-functionalization increases the oxygen exchange at saturation. Abstract : An easy method to achieve a fluorinated graphene oxide–silica nanohybrid (GOSF) is presented. Graphene oxide (GO) was synthesized by Hummer's modified method, the GO–silica nanohybrid (GOS) was obtained via Fischer esterification, the fluorinated moiety (3-pentadecafluoroheptyl-5-perfluorophenyl-1, 2, 4-oxadiazole) was introduced by nucleophilic substitution operated by the hydroxyl functionalities onto the GOS surface. Full characterization of the new materials confirmed the formation of covalent bonds between the graphene oxide/silica hybrid matrix and the fluorinated moieties. The proposed methodology offers an easy way to get fluorinated carbon/silica hybrid nanomaterials avoiding the harsh reaction conditions usually involved in the preparation of fluorinated materials, and allowing the selective immobilization of specific fluorotails. Moreover, performed oxygen uptake and release kinetics showed that the introduction of fluorinated moieties increases the oxygen exchange, making the material interesting for prospective applications in the biomedical field, as oxygen delivery system, as filler for biocompatible materials, and in the preparation of membranes for the purification of water.